Kajian Teologi Mengenai Angka 666 Menurut Wahyu 13:11-18 - Ekhat Binti Patangun; Abad Jaya Zega (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
Marking the number 666 on the forehead and hands of every person on earth (Revelation 13:16-18) is a form of forcing the entire population of the world to commit to the Dajjal. Apart from that, it is used as a guarantee of survival (can be traded) in the capitalist system created by Dajjal. Therefore, the number 666 is associated with the worship of the Dajjal and the practice of the global economic capitalism system. Because accepting the number 666 means worshiping and committing to the Antichrist, if Christians do this it means apostasy. The same thing also happens to us, namely on the forehead and our right hand bears the sign of Christ, symbolizing that our thoughts (forehead) are filled with the words of Christ and our deeds (right hand) produce good fruits that come from Christ by Christ and for Christ, or theologically, from God the Father, by God the Son and in the power of the Holy Spirit to glorify the Most Holy Trinity.